2005
DOI: 10.1002/mds.20265
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the course of Parkinson's disease under dopaminergic therapy: Performance of “fast tapping” is not a suitable parameter

Abstract: In addition to clinical rating scales, instrumental methods are employed frequently for assessment of performance or motor deficits in Parkinson's disease (PD). Many studies have analyzed such parameters in cross-sectional studies. We employed a battery of tests to investigate fine motor performance over a period of 4 years in 411 de novo parkinsonian patients from the Prado study. Specifically, tapping and pegboard testing ("plugging") were evaluated and performance on these tests compared with clinical ratin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 52 publications
1
7
0
1
Order By: Relevance
“…After discussion and review, rigidity and gait were considered outside the currently available technological and safety limitations of the program and therefore rejected. Selected domains and tasks were: tremor, assessed by a wrist accelerometer worn 2 full days weekly4; bradykinesia, assessed by alternating finger tapping (digitography) and hand tapping5; complex motor function, assessed by pegboard plugging; movement time and reaction time6, 7; and speech, assessed by vocal intensity decay and several other voice measures 8. Based on these recommendations, Intel Corporation developed the computer‐based AHTD which was tested in healthy subjects and then PD subjects with focus group patient feedback.…”
Section: Methodsmentioning
confidence: 99%
“…After discussion and review, rigidity and gait were considered outside the currently available technological and safety limitations of the program and therefore rejected. Selected domains and tasks were: tremor, assessed by a wrist accelerometer worn 2 full days weekly4; bradykinesia, assessed by alternating finger tapping (digitography) and hand tapping5; complex motor function, assessed by pegboard plugging; movement time and reaction time6, 7; and speech, assessed by vocal intensity decay and several other voice measures 8. Based on these recommendations, Intel Corporation developed the computer‐based AHTD which was tested in healthy subjects and then PD subjects with focus group patient feedback.…”
Section: Methodsmentioning
confidence: 99%
“…Yet this finding is perfectly in line with reports describing a higher incidence and more severe dyskinesias in the female sex. 6,7,9,10 Previous studies documenting differences in LID across genders suggested that they could reflect gender differences in L-dopa pharmacokinetics. In particular, the plasma L-dopa area-under-the-curve (AUC) is greater in women.…”
Section: Women Had More Severe Lids Before the Interventionmentioning
confidence: 97%
“…In particular, men need higher doses of L-dopa than women to achieve optimal therapeutic control, 7 while women are more frequently affected by L-dopa-induced dyskinesias. 6,7,9,10 As PD progresses, gender differences tend to become greater. In patients with a history of PD longer than 5 years, one study showed that men had worse motor function, as assessed by the United Parkinson's Disease Rating Scale (UPDRS) section III, thus indicating that motor signs and symptoms progressed faster in men than in women.…”
mentioning
confidence: 97%
“…26,[42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58] No studies of measurement properties in populations with PD were identified for the Box and Block Test, Clinical Rating Scale for Tremor, Coin Rotation Task, DASH, Fugl-Meyer Assessment, Movement Disorders Societysponsored revision of the UPDRS upper limb items, Minnesota Manual Dexterity Test, a or Scriptalyzer writing task. c Study sample sizes ranged from 12 to 411, and mean disease duration for most samples was >5 years.…”
Section: Part 2: Measurement Properties Of Upper Limb Toolsmentioning
confidence: 99%